(untitled) (Kuala Lumpur, Malaysia, 1993)
This study analyses the increased interdependence among the East Asian economies throughout the 1980s. Most countries in East Asia have adopted an outward-looking development strategy where international trade and investment have played important roles in their economies
Keywords: Đầu tư,Investments; Đông Á,East Asia